The Relationship Between School Bullying and Subjective Well-Being: The Mediating Effect of School Belonging - Xu, Zhuzhu; Fang, Chenchen (Frontiers in Psychology, 2021)
In order to deepen people's understanding of how school bullying influences subjective well-being of students involved, this research system explores the relationship between school bullying, school belonging, and subjective well-being, and the data of students in mainland China (represented by Beijing, Shanghai, Jiangsu and Zhejiang) participating in the PISA 2018 test were used for analysis. The results show that school bullying has a significant negative correlation between students' school belonging and subjective well-being. Besides, school belonging plays a part role in mediating the negative correlation between school bullying and subjective well-being of middle school.